Mindfull Eating To Increase Self Compassion Pada Pasien Diabetes Mellitus Tipe II - Ana Fitria Nusantara; Ainul Yaqin Salam (Pusat Riset dan Inovasi Nasional, 2023)
Type 2 diabetes mellitus is a chronic disease that is currently growing rapidly in society. The main target of diabetes management is to prevent complications and maintain a good quality of life. To achieve this target, sufferers need sufficient knowledge about DM management so that they are motivated and do it in the right way. Diet management plays an important role in stabilizing blood glucose. Mindful eating is a diet method that involves enjoying food without coercion so that sufferers can appreciate themselves more and the impact can improve the quality of life. This community service are carried out to increase the knowledge and ability of diabetes sufferers in carrying out diet management at home. The activities ini community services are providing education and skills training on how to carry out diet management using the mainstream eating method. The results of community service activities, show that participants have good understanding and abilities, high enthusiasm, interest in participating with great focus, and a strong commitment to implementing them in everyday life.